Evaluation of the Mechanical Behaviour of a DLC Film on Plasma Nitrided AISI 420 with Different Surface Finishing - Brühl, Sonia; Charadia, Raúl; Dalibón, Eugenia; Airoldi, Vladimir Trava; Cabo, Amado (International Conference on Plasma Surface Engineering, 2013)
Diamond-like-carbon films (DLC) are hard coatings with a very low friction coefficient, a high wear resistance and chemically inert. However, these coatings have adhesion problems on metallic substrates, because the high residual stresses in the DLC films cause failure of the interface between the film and the substrate. Different methods have been tested to improve the adhesion: deposition of interlayers, multilayer coatings between the substrate and the DLC film have been used as interface, chemical and physical modifications of the carbon coating or diffusion treatments of substrate surface. Plasma nitriding is a well-established method to harden stainless steels and can act as a pretreatment to increase adhesion and improve tribological behaviour of the DLC coating. Hopwever, the characteristics and phases of the nitrided layer can influence on the adhesion and the mechanical behaviour of the system. In this work, the mechanical behaviour of a DLC film deposited over non-nitrided and nitride martensitic stainless steel with two different surface finishing is studied.